Hubungan Antara Dukungan Keluarga Dan Peran Kader Dengan Keaktifan Kunjungan Lansia Ke Posyandu Pada Daerah Urban Di Kelurahan Kraton - Januarti, Luluk Fauziyah; Ardianti, Titin; Ekawati, heni; Priyanto, Agus (NHM PRESS, 2024)
Active visitation of the elderly Refers to how often or regularly the elderly (older people) attend or participate in visits to health facilities, public health programs, or other activities related to maintaining their health, the support needed to support the health of the elderly such as family support and the role of cadre. This research aims to analyze family support and the role of cadres in the activeness of elderly visits to posyandu, such as family support and the role of cadres. This research aims to analyze family support and the role of cadres in the activeness of elderly visits to posyandu. This research method is a cross-sectional analytical survey. Independent variables are family support and the role of elderly posyandu cadres and activeness of elderly visits. The population and sample were 46 elderly people in Kraton Bangkalan Village (Bangkalan Community Health Center Working Area) using a total sampling technique. The instrument uses a questionnaire. Analysis using Lambda (0.05). The research results showed that nearly half of elderly family support was insufficient, 22 (47.8%), the role of cadres was mostly sufficient, 33 (71.7%), the activeness of the elderly posyandu was mostly inactive, 26 (56.5%). From the results of the Lambda statistical test, a p value of 0.000 <a 0.05 was obtained. So it can be concluded that there is a relationship between family support and the elderly's activeness in participating in posyandu activities. From the results of the Lambda statistical test, the p value was 0.036 < a 0.05. So it can be concluded that there is a relationship between the role of cadres and the activeness of elderly people in participating in posyandu activities in urban areas in Kraton Subdistrict (Bangkalan Community Health Center Work Area). It is recommended that the elderly need to be given an understanding of the importance of participating in posyandu activities for their health. Education can be done through lectures, brochures and group discussions